2004
DOI: 10.1038/sj.bjc.6602244
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of peroxisome proliferator-activated receptor gamma in epithelial ovarian carcinoma

Abstract: The peroxisome proliferator-activated receptors (PPARs) belong to a subclass of nuclear hormone receptor that executes important cellular transcriptional functions. Previous studies have demonstrated the expression of PPARg in several tumours including colon, breast, bladder, prostate, lung and stomach. This study demonstrates the relative expression of PPARg in normal ovaries and different pathological grades of ovarian tumours of serous, mucinous, endometrioid, clear cell and mixed subtypes. A total of 56 ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 39 publications
6
59
0
2
Order By: Relevance
“…of ovarian carcinoma (Zhang et al, 2005). We have also demonstrated enhanced expression of ILK, a putative target gene of PPARb, in high-grade ovarian tumours (Ahmed et al, 2003) and the presence of cell-free irILK in the serum and ascites of ovarian cancer patients (Ahmed et al, 2004).…”
Section: Extent Of Staining In the Epitheliummentioning
confidence: 60%
“…of ovarian carcinoma (Zhang et al, 2005). We have also demonstrated enhanced expression of ILK, a putative target gene of PPARb, in high-grade ovarian tumours (Ahmed et al, 2003) and the presence of cell-free irILK in the serum and ascites of ovarian cancer patients (Ahmed et al, 2004).…”
Section: Extent Of Staining In the Epitheliummentioning
confidence: 60%
“…Moreover, in human pancreatic and ovarian cancers expression profiles indicate a strong overexpression of PPARc that positively correlate with higher pT stages and higher tumor grade. 29,30 Interestingly, our experiments showed that in Tg(HBV)CreKOc mice TZD administration inhibits tumor formation with a potency significantly higher than in parental and control mice. Moreover, PPARc ectopic expression in PPARc-deficient hepatocytes reduced the antiproliferative effect of TZD (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Since this antagonist has some off-target activity, we sup- pressed PPARγ expression by siRNA, and found that this also inhibited PGC-1α-induced apoptosis in Ho-8910 cells, supporting our interpretation that PGC-1α exerted its effect through a PPARγ-dependent pathway. Although PPARγ is upregulated in epithelial ovarian carcinoma [23], the downregulation of PGC-1α in epithelial ovarian cancer may restrain the activation of PPARγ-dependent apoptotic pathway, which could indirectly contribute to the development of ovarian tumor. However, the detailed molecular mechanisms need further study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent report shows that the expression of PPARγ is significantly enhanced in the late-stage epithelial ovarian carcinoma, indicating that PPARγ contributes significantly to the onset and progression of ovarian cancer [33]. Because the levels of PPARγ and the PPARγ coactivator, PGC-1α, are always linked to clinical outcome in patients with a variety of human cancers [12][13][14], it is reasonable to suspect that PGC-1α may also play a pivotal role in the pathogenic development of epithelial ovarian cancer.…”
Section: Pparγ Antagonist Suppresses Pgc-1α-induced Apoptosis In Ho-8mentioning
confidence: 99%
See 1 more Smart Citation